Guidelines proposal for a corrosion management model of the craft brewing industry in Bogotá - Moreno Amado, Myriam; Meza Buelvas, Liliana Margarita; Salamanca Sánchez, Harold Eduardo; Alonso Cardenas, Paula Andrea (Ingeniería Solidaria, 2026)
Introduction: Supported by Distrital Francisco José de Caldas University, this article presents a study on the guidelines for a corrosion management model for the craft brewing industry in Bogotá D.C., conducted in 2024 and 2025. Problem: Corrosion is a phenomenon that can lead to economic and material losses, health problems, and environmental issues caused by the deterioration of metallic equipment [1], [2], [3]. Objective: To propose guidelines for a corrosion management model in craft breweries that align with national and international standards. Methodology: A literature review was conducted on the factors that promote corrosion and the measures that minimize its economic and productive impact. This review took into account the characteristics identified during visits to craft breweries. Results: Guidelines were established for a corrosion management model with a cyclical structure that begins by identifying requirements and potential causes of corrosion, thereby developing a policy aligned with other management systems to foster continuous improvement. Conclusion: To make effective managerial decisions in the brewing industry, it is important to manage corrosion and to prevent and control the phenomenon in the face of economic and productive impacts. Originality: Fieldwork and theoretical analyses of corrosion, along with their integration into an organizational management system, offer an innovative approach to the brewing industry. Limitations: The proposed guidelines for a corrosion management model have not yet been implemented in the craft brewing industry.